THE IMPLEMENTATION OF INSTRUCTIONAL LEADERSHIP OF HEADMASTER AT MAN 1 PALU - A. Markarma; Darmawansyah; Masmur M (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The objectives of this research are: 1) To discover the description of the instructional leadership of Headmaster at Madrasah Aliyah Negeri 1 Palu; 2) To discover the strategy for implementing instructional leadership of headmaster at Madrasah Aliyah Negeri 1 Palu. The type of this research is descriptive-qualitative with a pedagogical, sociological and philosophical approaches. The data collection techniques are observation, interviews and documentation. The results of research showed that: 1) The application of instructional leadership is reflected on the leadership of headmaster which is oriented around improving the quality of education in Madrasah Aliyah Negeri 1 Palu; 2) The strategy for implementing instructional leadership of headmaster is by maximizing supervision and training at the level of school, and involving the teachers and educational staff in workshops or seminars to improve the quality of education in Madrasah Aliyah Negeri 1 Palu. The implications: 1) Headmaster needs to increase creativity in bringing up new ideas in directing and supervsing teachers and educational staff to improve the quality of educational services at Madrasah Aliyah Negeri 1 Palu; 2) Headmaster needs to implement strategies of supervision, discussion, training for teachers and educational staff, and involving parents of students in making policies relating to the improvement of quality of the learning process at Madrasah Aliyah Negeri 1 Palu.